2020
DOI: 10.1111/adj.12802
|View full text |Cite
|
Sign up to set email alerts
|

One‐year clinical evaluation of two high‐viscosity glass‐ionomer cements in class II restorations of primary molars

Abstract: Background: Little information exists on the clinical performance of restorative materials on primary teeth of preschool children. This study aimed to evaluate clinical performance of compomer, glass-hybrid-added high-viscosity glass-ionomer cement and zinc-added high-viscosity glass-ionomer cement materials in class ΙΙ restorations of primary molars. Methods: The study included 251 teeth of 57 patients aged 4-7 years with proximal caries in primary molars. The teeth were divided into three groups, and each re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…None of the studies were at high risk of bias in selection of the reported results. In 48.3% (n = 14) of studies the risk of bias was rated as “unclear” because of incomplete reporting of results for pre-specified outcome criteria (Alaki et al 2020 ; Deepa and Shobha 2010 ; Dermata et al 2018 ; El-Housseiny et al 2019 ; Ertugrul et al 2010 ; Gok Baba et al 2021 ; Hesse et al 2016 ; Hse and Wei 1997 ; Konde et al 2012 ; Lenzi et al 2017 ; Moura et al 2020 ; Olegario et al 2019 , 2020 ; Welbury et al 1991 ). The rest of the included studies reported the results completely (51.7%, n = 15).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…None of the studies were at high risk of bias in selection of the reported results. In 48.3% (n = 14) of studies the risk of bias was rated as “unclear” because of incomplete reporting of results for pre-specified outcome criteria (Alaki et al 2020 ; Deepa and Shobha 2010 ; Dermata et al 2018 ; El-Housseiny et al 2019 ; Ertugrul et al 2010 ; Gok Baba et al 2021 ; Hesse et al 2016 ; Hse and Wei 1997 ; Konde et al 2012 ; Lenzi et al 2017 ; Moura et al 2020 ; Olegario et al 2019 , 2020 ; Welbury et al 1991 ). The rest of the included studies reported the results completely (51.7%, n = 15).…”
Section: Resultsmentioning
confidence: 99%
“…The clinical performance of conventional (GIC), metal-reinforced (MRGIC), resin-modified (RMGIC), or high-viscosity glass-ionomer cements (HVGIC) was assessed in primary dentition in 9 included randomised controlled clinical trials (Akman and Tosun 2020 ; Alves dos Santos et al 2010 ; Dermata et al 2018 ; Dutta et al 2001 ; El-Housseiny et al 2019 ; Gok Baba et al 2021 ; Kilpatrick et al 1995 ; Kupietzky et al 2019 ; Welbury et al 1991 ). The comparators chosen were amalgam (Dutta et al 2001 ; Welbury et al 1991 ), compomer (Alves dos Santos et al 2010 ; Gok Baba et al 2021 ), composite resin (Akman and Tosun 2020 ; Alves dos Santos et al 2010 ; Dermata et al 2018 ; El-Housseiny et al 2019 ; Kupietzky et al 2019 ), bulk-fill composite resin (Akman and Tosun 2020 ), another type of glass-ionomer cement (Gok Baba et al 2021 ; Kilpatrick et al 1995 ), and glass carbomer (El-Housseiny et al 2019 ). One trial solely compared glass-ionomer cements (Kilpatrick et al 1995 ).…”
Section: Reported Outcomes For the Restorative Materialsmentioning
confidence: 99%
See 3 more Smart Citations